The Urgency Of Learning Quranic Sign Language Using HATI Method For Students Of Islamic Education Department UIN SMH Banten - Febriani, Ina Salmah; Ilyas, Deddy; Balqis, Ratu (Universitas Cokroaminoto Yogyakarta, 2024)
The development of inclusive learning methods is growing the needs of students in accordance with the directives of the Minister of National Education Number 70/2009 concerning Inclusive Education. The method of learning the Alquran in sign language is also of particular concern. This is reinforced by one of God's words in Qs. Al-Qamar/54 which is repeated four times in verses 17, 22, 32 and 40 regarding the guarantee that Allah makes it easy for the Alquran to be read, studied and memorized including those with the deaf. The importance of learning the Alquran in sign language, students of PAI department need to be equipped with competence regarding the sign language Alquran so that they have special abilities to teach the Alquran both in spoken and sign language. The learning method of the Alquran in sign language is certainly different from oral learning. However, even though the deaf do not use their voice when reading and memorizing the Qur'an, the deaf can still understand and interpret it (Azwar Hairul, 2022). In addition, learning the Alquran in sign language must at least go through three stages are therapy (oral and vocal), reading practice and practice (Ma'ruf P Subekti, 2020). Therefore, in order to create uniformity in learning the signed Alquran, Lajnah Pentashihan Mushaf Alquran (LPMQ) of the Ministry of Religion of the Republic of Indonesia and all deaf institutions and communities agreed on a form of the Alquran in sign language which can now be viewed live through the Indonesian Ministry of Religion's digital Alquran website https://quran.kemenag.go.id/. This paper will explain the importance of learning the Qur'an with signs with HATI methods can be applied to students as messengers of the Qur'an in the future in educational institutions and in society.